Analysis of Factors Influencing QRIS Usage in Banten, DKI Jakarta, and West Java Provinces - Yekti Widyaningsih; Galih Nur Kantaatmaja (Department of Statistics, Faculty of Mathematics and Natural Sciences, Universitas Islam Bandung, 2026)
Abstract. Quick Response Code Indonesian Standard is a non-cash payment method developed to support the digital transformation of Indonesia’s national payment system. Through a single QR code, various digital wallet applications and mobile banking platforms can be interconnected, offering convenience in transactions for both businesses and consumers. Although various factors, such as demographic differences and user behavior, are presumed to influence QRIS usage, there has been limited research exploring these aspects in depth. Therefore, this study aims to analyze the factors that influence QRIS usage by employing the ordinal logistic regression model, focusing on both demographic attributes and smartphone usage behavior. The ordinal logistic regression is a statistical technique designed to examine the relationship between an ordinal response variable and one or more independent variables. This model is suitable for analyzing data where the dependent variable consists of ordered categories. Overall, income and smartphone type emerge as consistently significant variables across all studied regions. Users with higher income levels and those using iOS-based smartphones tend to exhibit higher levels of QRIS usage compared to other groups. Based on the k-fold cross-validation method, the ordinal logistic regression model employed in this study yields an overall accuracy rate of 65.22%. These results indicate that both demographic factors and smartphone usage behavior have a significant impact on QRIS adoption in the observed regions.